POLA KUMAN DAN KEPEKAANNYA TERHADAP ANTIBIOTIK PADA SPESIMEN PUS YANG DIPERIKSA DI LABORATORIUM MIKROBIOLOGI FAKULTAS KEDOKTERAN UNIVERSITAS GADJAH MADA PADA TAHUN 2013 - , GALIH PRASETYA SAKADEWA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Backgrounds: One of the leading causes of death in the world is bacterial infection that is resistant to antibiotics. To monitor resistance patterns of bacteria in a hospital as wll as to track new bacteria strain that resistant to antibiotics, required periodic information regarding a particular sensitivity to the antimicrobial. Objectives: To determine the pattern of bacteria that are found in the pus specimens and resistance to antibiotics examined in the microbiology laboratory of the Faculty in 2013. Methods: This study is an observational descriptive study. Subjects were clinical isolates from the laboratory collection of pus specimens of Microbiology, Faculty of Medicine, University of Gadjah Mada. Results: The most common bacteria that we found are S. aureus 17 isolates (18%), S. epidermidis 15 isolates (15,9%), dan K. Penumonia 14 isolates (14,9%). Antibiotics that are found to be resistant are Penisilin G 86 isolates are resistant (81,5%), Erithromisin 67 isolates resistant (71,3%), and Cefiksim 67 isolates resistant (71,3%). Conclutions: The most common bacteria are S. aureus, S. epidermidis, and K. Pneumonia. The most resistance antibiotics are Penicillin G , Erithromisin, and Cefiksim.